Diversity, abundance and distribution of amoA-encoding archaea in deep-sea methane seep sediments of the Okhotsk Sea - Dang, Hongyue; Luan, Xi-Wu; Chen, Ruipeng; Zhang, Xiaoxia; Guo, Lizhong; Klotz, Martin G. (FEMS Microbiology Ecology, 2010)
The ecological characteristics of amoA-encoding archaea (AEA) in deep-sea sediments are largely unsolved. This paper aimed to study the diversity, structure, distribution and abundance of the archaeal community and especially its AEA components in the cold seep surface sediments of the Okhotsk Sea, a marginal sea harboring one of the largest methane hydrate reservoirs in the world. Diverse archaeal 16S rRNA gene sequences were identified, with the majority being related to sequences from other cold seep and methane-rich sediment environments. However, the AEA diversity and abundance were quite low as revealed by amoA gene analyses. Correlation analysis indicates that the abundance of the archaeal amoA genes was correlated with the sediment organic matter content. Thus, it is possible that the amoA-carrying archaea here might utilize organic matter for a living. The affiliation of certain archaeal amoA sequences to the GenBank sequences originally obtained from deep-sea hydrothermal vent environments indicated that the related AEA either have a wide range of temperature adaptation or they have a thermophilic evolutionary history in the modern cold deep-sea sediments of the Okhotsk Sea. The dominance of ammonia-oxidizing bacteria over AEA may indicate that bacteria play a significant role in nitrification in the Okhotsk Sea cold seep sediments. The authors would like to thank Jin Sun, Jian Sun, Liangliang Kong, Nianshuang Wang, Chunhui Wang, Linbao Zhang and Ying Zhang for their assistance in the project. This work was supported by China Ocean Mineral Resources R&D Association grants DYXM-115-02-2-20 and DYXM-115-02-2-6, Hi-Tech Research and Development Program of China grant 2007AA091903, China National Natural Science Foundation grant 40576069, National Basic Research Program of China grant 2009CB219506 and the Fundamental Research Funds for the Central Universities of China grant 09CX05005A. M. G. K. was funded by incentive funds provided by the UofL-EVPR office and the US National Science Foundation ...